Digitalization of government organizations: an empirical study of strategic factors of H.R. resources - Lili Khamiliyah; Agus Rahayu; Puspo Dewi Dirgantari; Lili Adi Wibowo; Eko Susanto (Cogent Business & Management)
The global shift towards digitalizing government organizations reflects citizens’ growing reliance on technology. This study explores the impact of strategic resources like data literacy, collaborative skills, and digital trust in government H.R. on digital culture, readiness, and overall digitalization. Despite numerous studies on digitalization in government organizations, limited attention has been given to the role of human resource (H.R.) strategic factors in shaping digital culture and readiness. Analyzing data from 257 government employees using SEM-PLS, the research highlights the crucial roles of data literacy and digital trust in shaping organizational digital culture. Moreover, it finds that digital culture and readiness significantly affect digitalization efforts. These findings not only enhance our understanding of digitalization in government but also validate existing technology adoption theories. The study offers a practical framework for evaluating digitalization performance, aiding policymakers and leaders in navigating digital transformation complexities. It stresses the importance of investing in human capital and fostering a supportive digital environment. Ultimately, such efforts are crucial for governments to effectively utilize digital technologies, improve service delivery, and address citizens’ evolving needs in an increasingly digital world.